A chaotic circuit under a new classification framework of inductorless Chua's circuits. Issue 4 (3rd October 2019) - Zhu, Lei; Pan, Minghai; Qiao, Xiaohua
Abstract : Purpose: This paper aims to classify the inductorless Chua's circuits into two types from the topological structures and construct a chaotic circuit under this new classification framework. Design/methodology/approach: In this paper, two types of inductorless Chua's circuit models are presented from topological structure, among which the first type of inductorless Chua's circuit (FTICC) model is much closer to the original Chua's circuit. Under this classification framework, a new inductorless Chua's circuit that belongs to the FTICC model is built by replacing LC parallel resonance of the original Chua's circuit with a second order Sallen–Key band pass filter. Findings: Compared with a paradigm of a reported inductorless Chua's circuit that belongs to the second type of inductorless Chua's circuit (STICC) model, the newly proposed circuit can present the attractors which are much more closely to the original Chua's attractors. The dynamical behaviors of coexisting period-doubling bifurcation patterns and boundary crisis are discovered in the newly proposed circuit from both numerical simulations and experimental measurements. Moreover, a crisis scenario is observed that unmixed pairs of symmetric coexisting limit cycles with period-3 traverse through the entire parameter interval between coexisting single-scroll chaotic attractors and double-scroll chaotic attractor. Originality/value: The newly constructed circuit enriches the family of inductorless Chua's circuits, and its simple topology with small printed circuit board size facilitates the various types of engineering applications based on chaos.